Review of the membrane and bipolar plates materials for conventional and unitized regenerative fuel cells - Dihrab, Salwan S.; Sopian, K.; Alghoula, M.A.; Sulaimana, M.Y.
Fuel cell or hydrogen systems offer the potential for clean, reliable and on-site energy generation. This article review current literature with the objective of identifying the latest development in membrane and bipolar plates for the conventional fuel cell and unitized regenerative fuel cell (URFC). The result shows that the choice of both the bipolar plates and the catalysts for URFC electrodes is a delicate task, for bipolar plate the corrosion in the oxygen side will be the major problem and for the electrodes a very good candidate for fuel cell mode will not function well in the electrolyser mode and therefore it is suggested that a compromise should be considered. It is recommended that aluminum, titanium or for best results titanium with a gold-coated layer is a suitable candidate as the bipolar plate and Pt/IrOX or Pt/Ru is suitable for an oxygen side catalyst in the URFC. For the conventional fuel cell the task is more easer because the corrosion problem is no more effective and thus the main goals for most of the studies was to concentrate on bipolar plate cost reduction, increase electrical conduction and reducing the platinum loading rate for catalyst
Keywords: FUEL CELL; BIPOLAR PLATE; UNITIZED; TITANIUM; MEMBRANE; CATALYST